Enforcement Of Human Rights In The Perspective Of Islam And Shariah In Indonesia - Yustitianingtyas, Levina; Krisnawati, Natasya Dellia (Socio Legal and Islamic Law, 2024)
The enforcement of human rights (HAM) from the perspective of Islam and Shariah in Indonesia reflects the state's commitment to accommodate the principles of justice and welfare in accordance with the teachings of Islam. The application of human rights in this context is in line with Shariah norms that emphasize the importance of protecting individual rights. In Indonesia, efforts to enforce human rights from an Islamic perspective are reflected through legal diversity that involves Shariah as a source of law. Enforcement of human rights in Islam involves aspects such as justice, freedom, and protection of individual rights. Indonesia constitutionally adheres to the principle of Bhinneka Tunggal Ika, which respects religious diversity, including Islam. Actions to enforce human rights in this context include protecting minority rights, religious freedom, and social justice. Additionally, cooperation among state institutions, civil society organizations, and Islamic institutions supports the implementation of human rights enforcement. However, challenges and criticisms regarding the implementation of human rights still arise, necessitating continuous efforts to strengthen human rights protection in accordance with Islamic values within the national legal context. Keywords: Human Rights, Islam, Shariah